Computational Study on Flexural Strengthening of Pre-cracks Reinforced Concrete Beams using Carbon Fibre Reinforced Polymer (CFRP) - Sukri, Amira Balqish; Koh, Heng Boon (Recent Trends in Civil Engineering and Built Environment, 2023)
Carbon fibre reinforced polymer (CFRP) composite has been frequently utilized for shear and flexural strengthening of RC structures in recent times. However, there are little attention has been paid to study or research for combination of the length and position of the CFRP need to be used in order to strengthen the RC beams. The objective of this study is to model the pre-cracks reinforced concrete beams by using finite element method, to investigate the capacity and crack pattern of pre-cracks reinforced concrete beams strengthened by CFRP with different length and position and to analyse the optimum arrangement of CFRP on flexural strengthening of pre-cracks reinforced concrete beams by using finite element analysis. The pre-cracks reinforced concrete beams were analysed using LUSAS software. In the FEA, the pre-cracks reinforced concrete beams were modelled as 2D surface element subjected to an incremental concentrated load. Nonlinear concrete material and CFRP was assigned to predict the structural behavior of pre-cracks reinforced concrete beams in terms of capacity and crack pattern with different length and position of CFRP. From the FEA, it was found that the capacity of beams increased as the length of CFRP increased. The crack pattern mostly appear at tensile zone as flexure cracks and shear cracks pattern at support area.